1-[3-(4-Chlorophenyl)-5-(4-methoxyphenyl)-4,5-dihydro-1H-pyrazol-1-yl]ethanone - Fun, Hoong-Kun (International Union of Crystallography, 2012)
In the title compound, C(18)H(17)ClN(2)O(2), the benzene rings form dihedral angles of 6.69 (6) and 74.88 (5)° with the 4,5-dihydro-1H-pyrazole ring. The benzene rings form a dihedral angle of 76.67 (5)° with each other. In the crystal, molecules are linked via bifurcated (C,C)–H⋯O hydrogen bonds into chains along [010]. The crystal structure is further consolidated by C—H⋯π interactions.